Handbook of biofuels production Processes and technologies - Luque, Rafael (Woodhead Publishing Ltd, 2010)
The global increase in the use of biofuels as substitute transportation fuels has prompted research and development into advanced chemical, biochemical and thermochemical biofuels production. This book provides a reference on the range of biomass conversion processes and technologies